Critical signaling molecules in the temporomandibular joint osteoarthritis under different magnitudes of mechanical stimulation - Liu, Yuqi; Jia, Fangwen; Li, Kangya; Liang, Chao; Lin, Xiao; Geng, Wei; Li, Yanxi (Frontiers in Pharmacology, 2024)
The mechanical stress environment in the temporomandibular joint (TMJ) is constantly changing due to daily mandibular movements. Therefore, TMJ tissues, such as condylar cartilage, the synovial membrane and discs, are influenced by different magnitudes of mechanical stimulation. Moderate mechanical stimulation is beneficial for maintaining homeostasis, whereas abnormal mechanical stimulation leads to degeneration and ultimately contributes to the development of temporomandibular joint osteoarthritis (TMJOA), which involves changes in critical signaling molecules. Under abnormal mechanical stimulation, compensatory molecules may prevent degenerative changes while decompensatory molecules aggravate. In this review, we summarize the critical signaling molecules that are stimulated by moderate or abnormal mechanical loading in TMJ tissues, mainly in condylar cartilage. Furthermore, we classify abnormal mechanical stimulationinduced molecules into compensatory or decompensatory molecules. Our aim is to understand the pathophysiological mechanism of TMJ dysfunction more deeply in the ever-changing mechanical environment, and then provide new ideas for discovering effective diagnostic and therapeutic targets in TMJOA.